2017
DOI: 10.1007/s00266-017-0977-x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Buccal Micro-Mucosa Free Graft combined with Posterior Scrotal Flap Transfer for Vaginoplasty in Male-To-Female Transsexuals: A Pilot Study

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…46 studies measured or reported on erogenous sensation of post‐surgical genitalia including the vulva, clitoris, anus, or mons pubis 11,13,18,19,30,33,35,44,45,48,51,66,67,70‐103 . General erogenous sensation ranged from 51.4% to 100% (median 97.7%) in 529 patients 11,13,30,74,80,88,89,91,100,101 . Only De Andrade (2013) reported a qualified scale for genital sensibility, receiving a 9.4/10 among 7 patients 75 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…46 studies measured or reported on erogenous sensation of post‐surgical genitalia including the vulva, clitoris, anus, or mons pubis 11,13,18,19,30,33,35,44,45,48,51,66,67,70‐103 . General erogenous sensation ranged from 51.4% to 100% (median 97.7%) in 529 patients 11,13,30,74,80,88,89,91,100,101 . Only De Andrade (2013) reported a qualified scale for genital sensibility, receiving a 9.4/10 among 7 patients 75 .…”
Section: Resultsmentioning
confidence: 99%
“…69 studies identified outcomes relating to sexual satisfaction/happiness of sex life and sexual function 11,16,29,31‐33,35‐39,41,44‐56,64,65,67,68,72,73,75‐79,85,86,94,95,98,99,101,102,106,107,114‐116,121,122,124,125,129,130,134,137,139,144,150,153‐160 . Satisfaction is included in FSFI, SPQ, BISF‐W, WHOQOL‐100, and Q‐SF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other less-invasive methods have been proposed, including Creatsas vaginoplasty (modified Williams method) [22], the labial and vestibular flap method [23], and the use of a small graft of perineal skin at the introitus to line the distal posterior aspect of the newly created vagina [24, 25]. In gender reassignment surgery, the most commonly used method is penile inversion vaginoplasty with scrotal flaps [26], sometimes combined with autologous buccal micro-mucosa free grafts [27]. However, several techniques have been attempted to cover (and epithelize) the newly formed vagina.…”
Section: Discussionmentioning
confidence: 99%